Capital structure and the issuance of corporate bonds in emerging Asia - Mizen, Paul; Packer, Frank; Remolona, Eli; Tsoukas, Serafeim (Edward Elgar, 2014)
In emerging Asia's local-currency bond market, the government bond segments have largely come of age while the corporate bond markets have remained immature. This paper focuses on the question of what drives corporate bond issuance, an issue of great practical relevance for policymakers in the region. We analyse the financing decisions of some 4,600 firms in eight countries in emerging Asia. We analyse these decisions within the context of the firms'capital structure. We also analyse the effect of market depth, relying on market-wide indicators from the BIS. We find that for both seasoned and unseasoned issuers, size and leverage both matter for the decision to issue. The availability of tangible assets matters for the decision to issue in foreign currency. At the level of the markets, the depth of the market and interest differentials matter.